PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA UD. TIMBUL DESA HILIANAA KECAMATAN IDANOGAWO KABUPATEN NIAS - Zai, Kristinfebriani (Universitas Nias Raya, 2023)
The aim of this research is to determine the influence of service quality on consumer satisfaction at UD. Timbul Hilianaa Village, Idanogawo District, Nias Regency. This type of research is quantitative. This type of research data is primary data, namely data obtained directly from respondents. The data source for this research is from consumers using a questionnaire, with the population and sample in this research being 96 respondents. The data analysis method used is simple regression analysis with a value of Y=19.499+0.545X. Based on the research results testing the hypothesis with a calculated value of 6.924>ttable 1.661, the researchers concluded that there is an influence of service quality on consumer satisfaction at UD. Timbul Hilianaa Village, Idanogawo District, Nias Regency. The suggestions for this research are (1) UD. It is very necessary to provide good service to consumers through communication to increase consumer satisfaction. (2) Maintaining and increasing the reliability of employees through accuracy and speed in providing services to purchasing consumers.